Phonon Spectra of Small Colloidal II-VI Semiconductor Nanocrystals. (14th September 2011) - Dzhagan, Volodymyr; Valakh, Mykhailo; Mel'nik, Nikolai; Rayevska, Olexandra; Lokteva, Irina; Kolny-Olesiak, Joanna; Zahn, Dietrich R. T.
Abstract : Resonant Raman spectroscopy has been employed to explore the first- and higher-order phonon spectra of several kinds of II-VI nanocrystals (NCs), with the aim of better understanding of the nature of phonon modes and forming a unified view onto the vibrational spectrum of semiconductor NCs. Particularly, besides the previously discussed TO, SO, LO, and 2LO modes, the combinational modes of TO+LO and SO+LO can be assumed to account for the lineshape of the spectrum below 2LO band. No trace of 2TO or 2SO band was detected, what can be the result of the dominance of Fröhlich mechanism in electron-phonon coupling in II-VI compounds. The resonant phonon Raman spectrum of NCs smaller than 2 nm is shown to be dominated by a broad feature similar to the SO mode of larger NCs or phonon density of states of a bulk crystal.